The perception of tactile feeling and corresponding textile attributes worldwide - Nagamatsu, R. N. (2018)
The textile industry has been exploring sensory analysis as means to evaluate different products as a strategy to improve product comfort. The sensory analysis uses a set of attributes standardized for sensory evaluation: the lexicons. This paper compares three lexicons developed to assess the sensory comfort of textile fabrics, by researchers from France, Portugal and Brazil. Quantitative Descriptive Analysis was conducted for the development of these lexicons. The study showed that France and Portugal have thirteen attributes in common and seven attributes are common in France, Portugal and Brazil: Light-Heavy, Gross-Fine, Fresh-Hot, Soft, Plushy, Elasticity and Falling.